Sonoviso y problemas sociales. Experiencia de educación superior a través de mediaciones para la toma de postura frente a experiencias del margen (2016)
Textual typology and objective. This article aims to describe the use of media in educational settings. In general, it has been one of the main lines of work of educators during the last decades. Hard work and always accompanied by the concern that the student is an active subject and a content producer. This is the motivation that led to the presentation of work with active pedagogies, such as Project Based Learning. In this case, the development of an audiovisual piece and an essay as a tool from which it was not only possible to promote the active role of students as an exercise of enunciation of points of view and own position, related to various social issues of common interest in the context of daily life.Methodology. After picking out the topics, the groups made up by students in the seventh semester of Social Communication chose the collection of stories and experiences from different social stuff, which facilitated the work of different topics of the course and motivated them to take up a critical position related to the aesthetical elaboration as a reflective exercise.Results. The work ended with a sample presented to the public, which ended up in the development of communicative and argumentative skills focused on the visibility of certain social problems and the consequent taking of a critical position. These topics belong to marginalized groups of the society, young people, men, women, homosexuals, mothers head of household, children, force displacement victims.